PENERAPAN MODEL PEMBELAJARAN POLA PERMAINAN KERJA KELOMPOK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR AKUNTANSI SISWA KELAS XI IPS SMA SWASTA ISLAM AL-ULUM MEDAN T.P 2013/2014 - Siti Aisyah (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2017)
The problem in this study is the low activity and learning outcomes of accounting students of class XI IPS SMA Islam Al - Ulum Lessons Year 2013/2014 in the learning process . The purpose of this study was to determine the activity and enhancing learning outcomes of accounting students XI IPS SMA Islam Al - Ulum Lessons Year 2013/2014 by applying a learning model Teamwork Game Pattern..This research is an action research ( Classroom Action Research ) was conducted in SMA Islam Al – Ulum Medan . The subjects were students of class XI IPS with the number of 40 students and the object of this research is to improve the activity and learning outcomes of accounting students through the learning model Teamwork Game Pattern . Data collection techniques in this study is to use the observation to see the students' learning activities and tests to see accounting student learning outcomes . The technique of data analysis using quantitative and qualitative data .The results ofthe analysis ofthe data o btainedpretest student learning outcomes of 40 students only10 students (25%) were completed. In the first cycleof student learning outcomes increased 17.5%, where students who completed up to 17 s tudents (42.5%). Although there was an increase from pretest to posttest in the first cycle, but has not reached 70% classical completeness. In the second cycleof student learning outcomes increased 47.5%, of which 36 students (90%) completed, and 4 students (10%) did not complete, in other words 70% of students have achieved the KKM>70. Observations indicate student activity by 25% the first cycle, the second cycle 82.5%, so there is a positive and significant improvement from the first cycletothe second cycle of 57.5%, in other words student active>71.88% .There are differences in improvement of learning outcomes are positive and significant accounting between cycles wher t coun t>t table is 17.38>2.02, with df =40-1 is df =39 at α=0.05. In other words Ha=X>Y is accepted and Ho is rejected. It can be concluded that the application of learning models Teamwork Game Pattern on the material ledger in class XI IPS SMA Islam Al-Ulum Medan TP 2013/2014 are proven to increase student learning outcomes are positive and significant. This means learning model Gaming Group Work Pattern s can beusedas an alternativet learning accountingKeywords : Activity Learning , Learning Outcomes , Learning Model Teamwork Game Pattern